Perinatal interventions for mothers and fathers who are survivors of childhood sexual abuse. (June 2018) - Stephenson, Lucy A.; Beck, Katherine; Busuulwa, Paula; Rosan, Camilla; Pariante, Carmine M.; Pawlby, Susan; Sethna, Vaheshta
Abstract: Childhood sexual abuse (CSA) is a worldwide problem with severe long-term consequences. A history of CSA can impact the childbearing experience of mothers and fathers; affecting their mental health, parenting skills and compromising infant development. Nonetheless, the perinatal period offers huge opportunity for intervention and hope. This literature review collates evidence for perinatal psychosocial interventions targeting both mothers and fathers who are survivors of CSA. Publications dating from 1970 to June 2016 were searched using Medline, Maternity and Infant Health, PsychINFO, PsychArticles, PubMed and the International Bibliography of the Social Sciences (IBSS). There were no perinatal interventions that considered the needs of survivor fathers. Sixteen publications on 9 psychosocial perinatal interventions for CSA survivors were identified. However, no sub-analyses specific to CSA survivors were reported. Trauma-specific perinatal interventions drew from a range of theoretical models and varied widely in format. Generally interventions were associated with improvements in maternal mental health, parenting competence, infant attachment security and positive public health outcomes. They were safe and feasible to implement, acceptable to parents and therapist, and therapists were able to implement protocols with adequate fidelity. Yet current data is hampered by small sample size, inconsistent reporting of CSA rates and outcome measures, scarcity of observational data and longer-term follow-up. Intervention modifications are proposed for CSA survivors in view of their unique childbearing experiences.